The Tragedy of the Commons and High Fertility, Social Mobility and Poverty in Tanzania Mainland (Tanzania Journal for Population studies and Development, 2012)
The demographic revolution reached Tanzania and other third world countries in an accelerated form. Pronatalists operate on grounds of an ahistorical demography and set aside this point because of ideology. They see no connection between high fertility and absolute poverty. Few scholars will now argue that in Sub-Saharan Africa rapid population growth is compatible with rapid economic growth. Even the Marxian argument that population growth will give rise to a multiplication of production units where capitalism is not developed in not tenable. Quite often the new units are lower in productivity and organization, and Malthusian types of hunger are common. Little vertical and intergenerational mobility in the Tanzanian society produced long-term fatalism, which is conducive to high fertility. It is argued that the tragedy of the commons in resources ownership, services and reproduction hinders social mobility and the evolution of a large middle class. The tragedy entrenches poverty and directly contributes to high fertility. Freedom in reproduction, like freedom in land use, brings ruin to all. It is shown that poor people have an idealistic view that they have the right to have many children, and these children have the right to education, health, land, etc., but what is missing in this idealistic view is an insistence that rights and responsibilities must go together. Asserting inalienable rights while ignoring or denying marching responsibilities brings ruin to all. Thus the paper concludes that that promoting a rapid evolution of a middle class may bring a more judicious balance between population and resources use.